DEVELOPING CONTEXTUAL TEACHING AND LEARNING-BASED LEARNING E-COMIC ON SOCIAL ARITHMETIC MATERIALS FOR JUNIOR HIGH SCHOOL GRADE VII - Dianing Meijayanti; bambang Sumarno (Universitas Negeri Yogyakarta, 2016)
AbstractThis research was aimed to develop e-comic learning based on Contextual Teaching and Learning (CTL) on mathematics learning arithmetic socials materials for junior high school grade VII, and to evaluate the products quality in terms of their validity, practicality, and effectiveness. This was a developmental research based on ADDIE model consisting of analysis, design, development, implementation, and evaluation. The developed were tried out to 32 students of grade VII-8 at SMP N 8 Yogyakarta. The instrument that used to evaluate the e-comic qualities consisted of e-comic assessment sheet for material and media experts, lesson plan assessment sheet, response questionnaire (for students and teacher), and student achievement test. The quality of e-comic learning in terms of validity was very good, according to the collected data that the e-comic obtained average score 8,23 and lesson plan obtained average score 8,32. In terms of practicality, they were good, according to the student response to the questionnaire obtained average score 4,00 and the teacher response to the questionnaire obtained average score 4,09. In terms of effectiveness, they were very good, according to the student achievement test, which was at percentage level 87,50%. Keywords: e-comic learning, CTL, arithmetic socials